THE BINARY SYSTEM OF TRANSLATION IDEOLOGY: BETWEEN FOREIGNIZATION AND DOMESTICATION - AKHMAD BAIHAQI (FKIP, Universitas Banten Jaya, 2019)
This paper is intended to understand how translation ideology occurs on students’ translation text of English Master Program at Postgraduate of University of Sultan Ageng Tirtayasa. The problem is formulated as follows; how does translation ideology occur on students’ translation text of English Master Program at Postgraduate of University of Sultan Ageng Tirtayasa. Data of the research resulted from the students’ translation text from English (SL) to Indonesian Language (TL). The result shows that the translation ideology of domestication is commonly occurred to avoid the awkwardness of the target text readers. This also makes the target texts have their readability and adjustability to TL culture and situation. On the contrary, the translation ideology of foreignization is mainly occurred to keep the relevance of the source text’s linguistic and cultural values.